2022
DOI: 10.15416/ijcp.2022.11.2.105
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Potentially Inappropriate Medications Identification Using Beers and STOPP Criteria in Hospitalized Geriatric Patients in Jakarta

Abstract: Adverse Drug Events (ADE) are closely related to Potentially Inappropriate Medications (PIMs) among the elderly, and can cause an increase in morbidity, mortality, and medical cost. The tools often used to assess PIMs include Beers and Screening Tool of Older Persons’ Prescriptions (STOPP) Criteria. Therefore, this study aimed to compare the PIMs identification using Beers 2019 and STOPP version 2 2016 Criteria. A descriptive-analytical method was used, and data were collected retrospectively from the medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The results of this study are in line with previous studies in which the number of drugs prescribed was significantly associated with the use of PIMs (p=0.001). The incidence of PIMs appeared 4.26 times higher in patients who received 10 or more drugs (Viviandhari et al, 2022). Likewise, the results of a study on the effect of the number of drugs prescribed on the risk of PIMs in elderly patients at a hospital in Lahore, Pakistan showed that polypharmacy (5-9 drugs) was associated with the incidence of PIMs with a value of p=0.012.…”
Section: Relationship Between Number Of Drugs and Duration Of Hospita...mentioning
confidence: 92%
“…The results of this study are in line with previous studies in which the number of drugs prescribed was significantly associated with the use of PIMs (p=0.001). The incidence of PIMs appeared 4.26 times higher in patients who received 10 or more drugs (Viviandhari et al, 2022). Likewise, the results of a study on the effect of the number of drugs prescribed on the risk of PIMs in elderly patients at a hospital in Lahore, Pakistan showed that polypharmacy (5-9 drugs) was associated with the incidence of PIMs with a value of p=0.012.…”
Section: Relationship Between Number Of Drugs and Duration Of Hospita...mentioning
confidence: 92%